Зміна образів в балеті «Кармен» коррелятивно до світових тенденцій розвитку культури ХХ – початку ХХІ ст. - Щербак, Є.В. (Культура народов Причерноморья, 2013)
Відстежується зміна хореографічних образів (зокрема жіночих) на прикладі балету
«Кармен» від пригніченої до вільної жінки коррелятивно до світових тенденцій розвитку культури ХХ –
початку ХХІ ст. у гендерній царині. Показується залученість до цих процесів українського
хореографічного мистецтва, передусім, у постановці «KAРМЕН.TV» (2006) Раду Поклітару.
Розглядається віддзеркалення феміністичної проблематики в західно-європейських та українських
балетних спектаклях ХХ – поч. ХХІ ст. На основні аналізу хореографічних образів робиться висновок
про їх еволюцію, відповідно до основних змін в культурі в сучасний період.
Ключові слова: балет, хореографічне мистецтво, гендер, жіночі образи, «Кармен-сюїта». Отслеживается изменение хореографических образов (в частности женских) на примере
балета «Кармен» от подавленной к свободной женщине коррелятивно мировым тенденциям развития
культуры ХХ – начала XXI века. в гендерной области. Показывается вовлеченность в эти процессы
украинского хореографического искусства, прежде всего, в постановке «KAРМЕН.TV» (2006) Раду
Поклитару. Рассматривается отражение феминистической проблематики в западно-европейских и
украинских балетных спектаклях ХХ – нач. XXI века. На основе анализа хореографических образов
делается вывод об их эволюции, согласно основным изменениям в культуре в современный период.
Ключевые слова: балет, хореографическое искусство, гендер, женские образы, «Кармен-сюита». By example of the ballet “Carmen” the changing of choreographic manner (particularly women)
from depressed to a free woman correlatively to world culture development tendencies of the ХХ- early XXI
century in the gender sphere is followed. First of all the involvement of the Ukrainian choreographic art to these
processes is shown in the performance “CARMEN.TV” (2006) Radu Poklitaru. The reflection of the feminist
range of problems in West- European and Ukrainian ballet performances of the ХХ – early XXI centuries is
considered. The influence and interconnection of the world culture development tendencies and choreographic
art with the transformation of the principal manners in the ballet performance “Carmen” by the foreign and
Ukrainian choreographers (A. Alonso, C. Goleizovskii, B. Stone, R. Petit, M. Eck, M. Born, R. Poklitaru).
Influence of the feminist movement on the replacement of the gender roles in dance performances, changing of
the plot-theme line of the authentic ballets for the more modern themes according to the world civilization
development. On the basis of the choreographic manners analysis the conclusion about their evolution
according to the main changes in the modern culture is made. With the help of the choreographic art which is a
reflection of this or that time, the picture of the existing cultural foundation is considered, and any changes or
tendencies influence ballet performances, their structural and ideological content. The emancipation effect also
took place in works of many West-European choreographers, however, this tendency can also be observed in the
Ukrainian dance art. One of the most important transformations in art connected with gender problems revision
is studied. In the beginning of the third quarter of the ХХ century the credibility gap to the modernism culture in
which men dominated, found the fullest expression in the art creators sphere. Following the west traditions of
the cultural development process the choreographic art had also underwent transformations.
Keywords: ballet, dance art, gender, images of women, "Carmen Suite".